Optimasi Pembelajaran Matematika dengan Menggunakan Game Based Learning Berbasis Kahoot: Analisis Minat Belajar Siswa Kelas VII SMP Negeri 1 Waikabubak - Watu, Angelita Yessi Duka Walu; Napu, Timotius Woda; Lede, Yulius Keremata (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to determine the effect of Kahoot-based Game Based Learning on the learning interest of seventh-grade students at SMP Negeri 1 Waikabubak in mathematics. The study used a quasi-experimental method with a pretest-posttest control group design. The study population consisted of all seventh-grade students at SMP Negeri 1 Waikabubak in the 2024/2025 academic year. The sample was selected using purposive sampling and consisted of two classes. Data were collected through a multiple-choice test consisting of 10 questions and a learning interest questionnaire containing 15 statements. The results showed that the use of Kahoot had a significant effect on students' learning interest. The significance value of the hypothesis test was 0.000 < 0.05, so H0 was rejected and Ha was accepted. The comparison of average scores also reinforces these results, with the control class mean of 49.42, while the experimental class reached 63.12. N-Gain analysis shows that the increase in learning interest in the control class was in the moderate category with an average of 0.52, while in the experimental class it was in the high category with an average of 0.80. Thus, it can be concluded that the application of Kahoot-based Game Based Learning can significantly increase student learning interest compared to conventional learning. These findings confirm that the integration of technology-based interactive learning media can be an effective strategy in increasing student engagement, especially in learning mathematics on algebraic operations in junior high school